Occurrence of Pestalotiopsis sp. on Ornamental Plants Camellia japonica L. in Romanian Public Gardens - Andreea-Mihaela Florea; Andrei-Mihai Gafencu; Florin-Daniel Lipșa; Iulian Gabur; Eugen Ulea (Horticulturae)
Camellias are evergreen shrubs native to the eastern and southern regions of Asia. In Romania, camellias are popular ornamental plants grown in pots. Pestalotiopsis species have a worldwide distribution and are pathogenic to a wide range of hosts. They also represent an important group of endophytes capable of producing a variety of bioactive secondary metabolites. This paper reports the occurrence of grey blight and twig or branch dieback caused by Pestalotiopsis sp. on Camellia japonica L. grown in pots and used in the landscaping of a public garden located in Iasi city, Romania (GPS coordinates: 47°09′24.0″ N 27°35′15.6″ E). Pestalotiopsis species were identified based on morphological characteristics and Sanger sequencing. Genomic analysis of the fungal isolate coded P_CJ_24, obtained from living plants, was based on ribosomal internal transcribed spacer region amplification using the LSU primers. This first report of Pestalotiopsis species infection of ornamental plants in Romania suggests that new plant pathogens can be introduced in new environmental conditions through plant pods and their incidence increases with the widespread of plant material among gardens.